Mindfulness-Based Intervention to Lower Post-Traumatic Stress Disorder in Survivors of Domestic Violence - Hartono, Vincent Eddy Kuncoro; Hasanat, Nida Ul (Faculty of Psychology, Universitas Gadjah Mada, 2026)
This study aimed to reduce post-traumatic stress disorder (PTSD) levels in survivors of domestic violence (DV) through a mindfulness-based intervention program modified from Brief Mindfulness-Based Stress Reduction (BMBSR) and Mindfulness-Based Distress Management Training. Seven female DV survivors were involved in the program, which consisted of six meetings over three weeks. The participants practiced breathing meditation, body-scan meditation, loving-kindness meditation, and sitting meditation. They also performed walking meditation, eating meditation, and mindful yoga. The study used a quasi-experimental one-group pre-test post-test design, and the author measured the participants' PTSD using the Impact of Event Scale - Revised (IES-R). The results of analysis using the Wilcoxon Signed Rank Test showed a significant difference in PTSD scores, with a Z value of -2.366 (p< .05), which indicates that the mindfulness-based intervention used in this study can significantly lower PTSD in domestic violence survivors. Participants experienced a reduction in intrusion (recurrence of traumatic events), avoidance (avoidance of stimuli), and hypervigilance (excessive response to stimuli).